2002
DOI: 10.1017/s1357729800052188
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and nutritional effects on lactational performance of gilts selected for components of efficient lean growth

Abstract: Lactational performance was measured in Large White gilts from lines that had been divergently selected over seven generations for daily food intake (DFI), lean food conversion ratio (LFC), lean growth rate with ad-libitum (LGA) or restricted (LGS) feeding during performance test. Control line gilts were included in the study. During the lactation period of 21 days, gilts were given to appetite five isoenergetic diets differing in ileal digestible lysine: energy (0·40, 0·58, 0·76, 0·94 and 1·12 g/MJ digestible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
9
3
Order By: Relevance
“…Selection for increased daily FI of grower-finishers resulted in greater backfat thickness at start of lactation. The results of Cameron et al (2002) were in line with our results. The only exception was the genetic correlation of FI as a grower-finisher and FI during lactation, which was, although small, positive in our study.…”
Section: Feed Intake During Finishing and During Lactationsupporting
confidence: 91%
See 1 more Smart Citation
“…Selection for increased daily FI of grower-finishers resulted in greater backfat thickness at start of lactation. The results of Cameron et al (2002) were in line with our results. The only exception was the genetic correlation of FI as a grower-finisher and FI during lactation, which was, although small, positive in our study.…”
Section: Feed Intake During Finishing and During Lactationsupporting
confidence: 91%
“…This might explain the relatively low genetic correlation for FI with FI as a grower-finisher. Cameron et al (2002) compared lactation performance in Large White gihs between lines that had been divergently selected for daily FI during growing-finishing. Lactation FI did not differ significantly between these selection lines, nor did BW.…”
Section: Feed Intake During Finishing and During Lactationmentioning
confidence: 99%
“…Cameron et al . () reported that in a population divergently selected for feed intake in the growing pig, selection for improved feed conversion ratio was genetically associated with a numerical reduction in feed intake levels and increased mobilization of body reserves during lactation.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, direct selection for feed conversion and leanness has been indirectly linked to reduced intake capacity in the long term, reducing sow feed intake and longevity (Hermesch ), and selection for efficient lean growth has resulted in leaner gilts and sows which have fewer body reserves available for mobilization when feed intake during lactation is inadequate (Cameron et al . ). The inclusion of LFI traits in a selection index may provide a sufficient method for improvement as several studies have indicated potential for increasing levels of LFI through direct selection (Lewis & Bunter ; Yoder et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation